Severity of Expert-Identified Behavioural Responses of Humpback Whale, Minke Whale, and Northern Bottlenose Whale to Naval Sonar: - Sivle, L.D.; Kvadsheim, P.H.; Cure, C.; Isojunno, S.; Wensveen, P.J.; Lam, F.P.A.; Visser, F.; Kleivane, L.; Tyack, P.L.; Harris, C.M.; Miller, P.J.O. (2015)
Controlled exposure experiments using 1 to2 kHz sonar signals were conducted with 11 humpback whales (Megaptera novaeangliae), one minke whale (Balaenoptera acutorostrata), and one northern bottlenose whale (Hyperoodon ampullatus) during three field trials from 2011 to 2013. Ship approaches without sonar transmis-sions, playbacks of killer whale vocalizations, and broadband noise were conducted as controls. Behavioural parameters such as horizontal movement, diving, social interactions, and vocalizations were recorded by animal-attached tags and by visual and acoustic tracking. Based on these data, two expert panels independently scored the severity of behavioural changes that were judged likely to be responses to the experimental stimuli, using a severity scale ranging from no effect (0) to high potential to affect vital rates (9) if exposed repeatedly. After scoring, consensus was reached with a third-party moderator. In humpback whales, killer whale playbacks induced more severe responses than sonar exposure, and both sonar exposures and killer whale playbacks induced more responses and responses of higher severity than the no-sonar ship approaches and broadband noise playbacks. The most common response during sonar exposures in all three species was avoidance of the sound source. The most severe responses to sonar (severity 8) were progressive high-speed avoidance by the minke whale and long-term area avoidance by the bottlenose whale. Other severe responses included prolonged avoidance and cessation of feeding (severity 7). The minke whale and bottlenose whale started avoiding the source at a received sound pressure level (SPL) of 146 and 130 dB re 1 μPa, respectively. Humpback whales generally had less severe responses that were triggered at higher received levels. The probability of severity scores with the potential to affect vital rates increased with increasing sound exposure level (SEL). The single experiments with minke and bottlenose whales suggest they have greater susceptibility to sonar disturbance than humpback whales, but additional studies are needed to confirm this result.